Evolução diferencial para problemas de otimização restrita - Silva, Eduardo Krempser da (2015)
Made available in DSpace on 2015-03-04T18:51:14Z (GMT). No. of bitstreams: 1 dissertacao_eduardo_krempser.pdf: 675502 bytes, checksum: 9909466baacd7f6cebcd6029c53ed6c4 (MD5) Previous issue date: 2009-03-04